Determination of Circulating Immune Complexes in Patients with Malignant and Pre-malignant Disease: A Case Study in South-Eastern Nigeria - Chukwurah, E. F.; Emele, F. E.; Iyare, F. E.; Nwigwe, C. G.; Ogbodo, S. O. (Research Highlights in Disease and Health Research Vol. 6, 2023)
The present study aimed to establish possible correlative significance between the detection and concentration of circulating immune complexes and disease progression in women with premalignant conditions of the breast and those with various stages of breast cancer before and after any form of treatment. Breast cancer is the most common cancer among women worldwide and is still incurable. Breast cancer is more common in Nigeria thanks to late presentation and a dismal clinical outcome. The existence of tumor neoantigens in human breast cancer cells has long been demonstrated, and these antigens may produce particular circulating immune complexes depending on the genetic variations and expressions in various racial/ethnic groups. Breast cancer has been linked to circulating immune complexes, which are useful in advanced nations for determining diagnosis, prognosis, and treatment response. This is a prospective study conducted between October 2012 and February 2015. Circulating immune complexes were estimated in 64 breast cancer (24 early stage and 40 advanced stage breast cancer), 40 benign breast tumour patients and 40 apparently healthy age-matched control subjects by immunoenzymatic assay. The subjects were recruited from two hospitals in Ebonyi and Enugu States, Nigeria. The CIC estimation was done in pre-treatment and at intervals (3 and 6 months) after various forms of treatment in cancer patients and benign breast tumor and results compared. Biological markers are widely recognized as important tools in the evaluation and management of patients with cancer. Our results showed incidence of raised pre-treatment CIC in 28%, 15% and 0.05% of the breast cancer patients, benign breast tumor and apparently healthy age-matched control respectively. No significant differences in CIC were found between treatment and disease groups. The highest levels in mean CIC were seen in the advanced stage breast cancer patients and the mean value was greater than that of the controls. The diagnostic value of CIC is thus questioned, most likely as a result of the environment's increased immunocomplex formation triggers. Therefore, in this racial/ethnic environment, the development of antigen-specific CIC determinations that may have diagnostic and/or prognostic value is necessary. Need for continuous search for tumour antigen-specific immune complexes is advocated.